2018
DOI: 10.1121/1.5033330
|View full text |Cite
|
Sign up to set email alerts
|

How the acoustic resonances of the subglottal tract affect the impedance spectrum measured through the lips

Abstract: Experimental determinations of the acoustic properties of the subglottal airway, from the trachea below the larynx to the lungs, may provide useful information for detecting airway pathologies and aid in the understanding of vocal fold auto-oscillation. Here, minimally invasive, high precision impedance measurements are made through the lips (7 men, 3 women) over the range 14-4200 Hz during inspiration, expiration, and with a closed glottis. Closed glottis measurements show the expected resonances and anti-res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…The result was consistent with Wohl (1985, 1986), which showed a strong correlation between trachea length and height and no correlation between trachea length and gender when the effect of height was eliminated. In a recent study by Hanna et al (2018), SGRs estimated using this tube model were found to be in agreement with SGRs obtained from input impedance measurements performed at the lips. However, a consequence of using this tube model is that the ratios between the first three SGRs are assumed to be constant across all speakers, which was a major implication of Lulich et al (2012).…”
Section: Introductionsupporting
confidence: 70%
“…The result was consistent with Wohl (1985, 1986), which showed a strong correlation between trachea length and height and no correlation between trachea length and gender when the effect of height was eliminated. In a recent study by Hanna et al (2018), SGRs estimated using this tube model were found to be in agreement with SGRs obtained from input impedance measurements performed at the lips. However, a consequence of using this tube model is that the ratios between the first three SGRs are assumed to be constant across all speakers, which was a major implication of Lulich et al (2012).…”
Section: Introductionsupporting
confidence: 70%
“…Subglottal resonances have been investigated in both adults (Chi and Sonderegger, 2007;Cranen and Boves, 1987;Csapo et al, 2009;Dogil et al, 2010;Hanna et al, 2018;Ishizaka et al, 1976;Lulich, 2010;Lulich et al, 2012;van den Berg, 1960) and in children (Lulich, 2010;Lulich et al, 2011b;Yeung et al, 2018). Among children in the age range 6-to 9-years-old, the mean frequency of F Sg1 was 780 Hz in 3 boys, 2 girls (Lulich et al, 2011b) and 744 Hz in 12 boys and 3 girls (Yeung et al, 2018).…”
Section: A Acoustic Variablesmentioning
confidence: 99%
“…Acoustic studies of wind instrument players have shown that the body of the player has very appreciable effects on the sound waves produced, not only with respect to amplitude and frequency or ease of performing, but also as a resonating chamber that alters the acoustic profile of the instrument itself (cf. Li et al 2015;Boutin et al 2015;Hanna et al 2018). Furthermore, in most wind instruments, the sound wave finishes outside of the instrument -that is, the final antinode of a sound wave touches the inside of the instrument, but the final node, which determines its frequency, is actually beyond the edge of the instrument.…”
Section: Introductionmentioning
confidence: 99%